Picket fastening methods in ostrog walls in Siberia and the Far East in the late 16th — early 18th century - Gorokhov S.V. (Вестник археологии, антропологии и этнографии)
Until now, the topic concerning the variety of ways of fastening individual logs into a palisade wall has remained out of sight of researchers. In fact, only one fastening method has been presented in historiography — “on pins”. However, not all authors associate the historical term “on pins” and the respective method of fastening — “dovetail attachment”. The purpose of the study, the results of which are presented in this article, was to identify and reconstruct all ways of individual log fastening into a palisade wall. The source base is represented by materials of archaeological excavations of wooden fortifications in Siberia, data from written sources that contain a description of fortifications in the Russian state, ethnographic data from Transbaikalia and Kostroma region, and graphical sources. The main research method was analytical comparison of the content of various fragmentary data characterizing different aspects of the same construction techniques. This allowed us to develop a holistic perception of each method of fastening logs in a palisade. During the study, it has been found that the term “on pins” does indicate a “dovetail attachment”. The manufacturing method of pin has been reconstructed, and its length has been determined analytically. The technology of erecting of a palisade wall “on pins” has been reco-vered. A criterion for attributing the palisade to the one on one or the one on two pins has been formulated. For the first time, such method of attachment of logs as “spike-groove” has been revealed: in the lower and/or upper parts of the pickets spikes were made, on which a block with grooves was hooked. Archaeological characteristics of a palisade with such fastening method of logs have been identified. Joining of adjacent logs into a longitudinal groove, and also with ropes, has been attributed to one of the methods of picket fastening. Fastening of logs in a thinned palisade (with a certain distance maintained between neighboring pickets) was achieved in a specific way. Two symmetrical grooves were selected in the upper quarter of the log. Then, a hole was made in the resulting partition, through which a beam was passed. Along with the “dovetail attachment” and with the help of the beam, an essential way of log fastening was their deepening into the ground. As a result of this research, it has also been found that the “pereklady” (crosspiece) structural element is not related to the methods of fastening logs in the palisade wall.